Analysis of Causal Factors and Impact of Legal Uncertainty on Building Rights from Management Rights - Permadi, Iwan (Jurnal Dinamika Hukum, 2024)
Legal uncertainty faced by holders of Building Rights (HGB) derived from Land Management Rights (HPL) in Indonesia is a pressing issue that creates difficulties in maintaining and changing the status of their rights, negatively impacting their welfare and the overall land system, which this study aims to examine and address.  This study uses normative legal research methods with legislative, conceptual, comparative, and case approaches. Data were collected through literature studies and analyzed qualitatively and descriptively by considering interdisciplinary aspects. Factors that cause legal uncertainty include lack of legal protection, regulatory uncertainty, ineffective legal implementation, and reliance on third parties. This impacts the difficulty of maintaining HGB, the limitation of changing rights status, and implications for people's welfare. The findings indicate the need for legal reform, increased transparency, and strengthening institutional capacity. The implications of the findings encourage the improvement of a more fair, efficient, and legal system for HGB holders. This research is important to identify the root cause of the problem and formulate recommendations for improving the soil system. Further research suggestions include comparative empirical, interdisciplinary, and action research to implement solutions.